Egyptian evidence -based pediatric clinical practice adapted guidelines for management of [1] steroid sensitive nephrotic syndrome (EPG/SSNS 2022) - Bahia Moustafa; Mahmoud M. El-Kersh; Sherin Shalaby; Nancy Abdel Salam; Sawsan Moselhy; Gamal Taha Soliman; Abeer Selim; Yasser S Amer; Ashraf Abdel Baky; On Behalf of the Egyptian Pediatric Clinical Practice Guidelines (EPG) (SpringerOpen, 2023)
Abstract Background Nephrotic syndrome is one of the most common chronic kidney diseases in children. Steroid sensitive type constitutes about 90% and steroid resistant 10% of total cases.  Objectives These national adapted guidelines aim to frame evidence-based recommendations adopted or adapted from IPNA 2020, KDIGO 2021, and Japanese 2014 for diagnosis, evaluation, management and follow-up of nephrotic children for Steroid sensitive nephrotic syndrome (SSNS) as paper one to be followed with SRNS as paper two. Methodology Formulation of key questions was followed with review of literature, guided by our retrieved and appraised guidelines using Agree plus appraisal tool. After virtual monthly meetings through the year 2021, the final draft was validated considering the comments of external local reviewers and KDIGO-assigned reviewers.  Discussion Rationale behind the selection of adopted statements and tailoring of others to suit our local facilities' expertise and disease profile was discussed in the text with reasons. Conclusion The provided guidelines aim to optimize patient care and outcome and suggest research areas lacking validated research recommendations.